Ilmu Dan Pendidikan Ditinjau Dari Surat Al-‘Alaq Ayat 1-5 - sudarto, sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
Science is a conscious effort to investigate, find to increase human understanding from various aspects of reality in the human realm. These aspects are limited so that a definitive formula is produced. Education discusses the process of reciprocal adjustment between humans and humans and nature with regular development and refinement of all moral, intellectual and physical potential. Education is a basic effort to prepare students through activities of guidance, teaching and training. While education as a phenomenon is the event of an encounter between two or more people whose impact is the development of a life view, attitude of life, or life skills that is one or several parties, both of which must be breathed or inspired by Islamic teachings and values. The Qur'an has repeatedly explained the importance of knowledge. Education is not only about science but also about morals so that it can be balanced and also able to carry out tasks as servants of Allah Almighty and the Caliph in the face of the earth with Islamic teaching values. God repeats the command to read 2 times, because according to the habit, one can read something smoothly after repeating it several times, so also in seeking knowledge we cannot automatically grasp the knowledge given by the teacher but try to write, memorize, and practice it. God teaches all knowledge, and with that knowledge we are different from animals that have no reason, so as humans we should always seek knowledge and practice it throughout life. Keyword : science, educations, qs. al-alaq